Comparison of two biodegradable‐polymer‐based sirolimus‐eluting stents with varying elution and absorption kinetics in patients with acute myocardial infarction: A subgroup analysis of the PANDA III trial. (21st January 2017) - Guan, Changdong; Xu, Bo; Qiao, Shubin; Qin, Lei; Li, Yi; Li, Zhanquan; Guo, Yong; Sun, Zhongwei; Song, Lei; Gao, Runlin; ,
Abstract : Background: Implantation of early‐generation metallic drug‐eluting stents (DES) in patients with acute myocardial infarction (AMI) is associated with poor vessel wall healing. Use of biodegradable polymer (BP) DES might improve safety outcomes; however, the impact of varying drug elution and polymer absorption kinetics of BP‐DES on clinical outcomes in the AMI population is unknown. Methods: This subgroup analysis of the randomized PANDA III trial included 732 patients (366 in each group) presenting with recent (<1 month) AMI. Primary endpoint was 1‐year target lesion failure (TLF), a composite of cardiac death, target vessel myocardial infarction (MI), or ischemia‐driven target lesion revascularization. Secondary endpoints included a patient‐oriented composite endpoint (PoCE) of all‐cause death, all MI, or any revascularization; individual TLF and PoCE components; and definite/probable stent thrombosis (ST). Results: There were no significant differences between‐groups in baseline clinical, angiographic, or procedural characteristics other than the proportion of post‐dilatation, which was performed more frequently with the BuMA stent (53.9% vs. 44.5%; P  = 0.004). After 1 year, compared to Excel SES implantation in patients with AMI, BuMA was associated with similar incidences of TLF and PoCE (5.5% vs. 8.3%, P  = 0.14; 8.8% vs. 9.9%, P  = 0.61, respectively) but lower incidences of MI (2.5% vs. 6.1%, P  = 0.02), target vessel MI (2.2% vs. 5.8%, P  = 0.01), and definite/probable ST (0.3% vs. 2.2%, P  = 0.04). Conclusions: BuMA SES, with faster drug elution rate and polymer absorption kinetics, might improve safety outcomes compared to Excel SES in the high‐risk AMI population. © 2017 Wiley Periodicals, Inc.